TRANSFER KNOWLEDGE: PENGENDALIAN GULMA AIR SUPAN-SUPAN DI LAHAN BASAH KECAMATAN SUNGAI TABUK MELALUI PENGOMPOSAN SEDERHANA MENUJU KEMANDIRIAN PUPUK - Muhammad Yazid Rafif; Arlita Maharani Latifah; Bela Audina; Latipah Latipah; Lusi Mahdini; Nisa Alfitri; Nor Abidah; Siti Hanna Maya Gading; Muhammad Ikhsan Rufaqo Alfarizi; Nazwa Aisya; Haliza Debby Savitri; Fakhrina Istiqomah; Muhammad Sahid; Raudhatul Jannah; Riza Adrianoor Saputra; Untung Santoso; Yulia Padma Sari; Ronny Mulyawan; Rina Lestari (Jurnal Abdi Insani, 2026)
The aquatic weed supan-supan (Neptunia oleracea L.) is an invasive species commonly found in wetlands and has the potential to disrupt agricultural activities. To date, this weed has generally not been optimally utilized by local communities and is often regarded as agricultural waste. This village development program aimed to enhance community knowledge and skills in controlling the aquatic weed supan-supan through its utilization as a raw material for compost production. The activity was conducted in Sungai Pinang Lama Village, Sungai Tabuk District, Banjar Regency, targeting farmer groups and women farmer groups affiliated with the Setia Kawan Farmers Association. The implementation method employed a transfer of knowledge approach, including extension activities, training sessions, and hands-on practice in compost production using supan-supan biomass. Program evaluation was carried out using pre- and post-extension questionnaires to assess improvements in participants’ knowledge. The results showed an increase in participants’ knowledge regarding the benefits of supan-supan by 61.54%, knowledge of composting microorganism activators by 46.15%, and knowledge of organic fertilizer production through fermentation systems by 38.46%. In addition, participants’ awareness of the abundance of supan-supan increased by 15.38%, and agreement that organic fertilizer can reduce agricultural operational costs increased by 7.69%. To ensure the sustainability of the ULM Berdampak 2025 Village Development Program, it is recommended that participants disseminate the knowledge gained from this activity to group members who were unable to attend, so that all farmers may benefit from the training and knowledge transfer.